A TYPOLOGICAL RARUM IN SOGDIAN: OVERT COMPLEMENTIZERS IN INDICATIVE ROOT CLAUSES - Franco, Ludovico (Lingua Posnaniensis, 2013)
The purpose of this work is to illustrate an extremely rare linguistic feature, namely the overt present of a root complementizer in assertive/indicative (i.e. unmarked) matrix clauses, of the Sogdian language, an Eastern Middle Iranian Language once spoken in a region located in the valley of rivers Zaravshan and Kashkadarya (roughly corresponding to the territory of modern day Uzbekistan and Tajikistan). This linguistic fact is very interesting because it represents an overt evidence of the principle of endocentricity inferred in the Generative tradition since the early 80s. In comparative perspective, this uncommon feature of the Sogdian language may be associated to the mechanism of para-hypotaxis, previously studied in many different Romance languages (e.g. Old French, Old Italian, Old Catalan) and recently discovered in other genetically unrelated languages (e.g. Swahili, Zamucoan languages)